Study of dissolution profiles of Аmlodipine tablets with enalapril - Behei, Nataliia; Tryhubchak, Oksana (The Ukrainian Scientific Medical Youth Journal, 2022)
quality assurance in the production of medicines is a comprehensive concept. The quality of medicines must be guaranteed at all stages of production - from development, research and production to implementation and optimal use. All this is included in the requirements of a number of good practices: GMP, GLP, GCP, GDP, GPP, GSP. Great importance in the development of solid dosage forms is given to the study of the degree of release rate of active substances and in environments with different acidity indicators. To assess the quality of the developed combined tablets of amlodipine with enalapril, to predict the rate of release of active substances from them, and accordingly the manifestation of therapeutic effect on the body, the aim was to study the dissolution profiles of amlodipine tablets with enalapril in comparison with the original drug, which contains one active substance. The subjects of the study were Amlodipine with enalapril, 5 mg / 5 mg tablets and the corresponding original monopreparations: Norvask, 5 mg tablets (amlodipine) and Berlipril, 5 mg tablets (enalapril). The studies were performed according to pharmacopoeial requirements using a device for dissolving USP I (shovels). Dissolution media - 900 ml of buffer solutions pH 1.2, pH 4.5 and pH 6.8. The analysis was performed by high performance liquid chromatography. A solution of potassium dihydrogen phosphate in water (pH 4.0) was used as the mobile phase. Detection was performed at a wavelength of 215 nm. Comparative studies of the dissolution kinetics of Amlodipine with enalapril, 5 mg / 5 mg tablets with the dissolution kinetics of the original Norvasc drugs, 5 mg tablets and Berlipril 5 mg tablets were performed. It was found that after 15 min in a pH of 6.8 enalapril maleate is released from the developed combination tablets by only 83.6%, and within 30 minutes there was a complete release of both active pharmaceutical ingredients in all study media. A high value of the factor of similarity of the dissolution profile of the developed drug Amlodipine with enalapril, tablets 5 mg / 5 mg to the original monopreparations: pH 1.2 amlodipine - 92.3, enalapril - 86.5; pH 4.5 amlodipine - 94.8, enalapril - 86.3; pH 6.8 amlodipine - 96.2, enalapril - 80.2. It was determined that the biopharmaceutical factors, which include the physicochemical properties of amlodipine and enalapril, the composition of excipients, features of the technological process, have an impact on the dissolution kinetics of the study drug based on amlodipine and enalapril. Therefore, the proposed combined tablets of amlodipine with enalapril are similar to the corresponding reference monopreparations and can find use in experimental and practical medicine.